Veterinary applications of pulsed electromagnetic field therapy. (August 2018) - Gaynor, James S.; Hagberg, Sean; Gurfein, Blake T.
Abstract: Pulsed electromagnetic field (PEMF) therapy can non-invasively treat a variety of pathologies by delivering electric and magnetic fields to tissues via inductive coils. The electromagnetic fields generated by these devices have been found to affect a variety of biological processes and basic science understanding of the underlying mechanisms of action of PEMF treatment has accelerated in the last 10 years. Accumulating clinical evidence supports the use of PEMF therapy in both animals and humans for specific clinical indications including bone healing, wound healing, osteoarthritis and inflammation, and treatment of post-operative pain and edema. While there is some confusion about PEMF as a clinical treatment modality, it is increasingly being prescribed by veterinarians. In an effort to unravel the confusion surrounding PEMF devices, this article reviews important PEMF history, device taxonomy, mechanisms of action, basic science and clinical evidence, and relevant trends in veterinary medicine. The data reviewed underscore the usefulness of PEMF treatment as a safe, non-invasive treatment modality that has the potential to become an important stand-alone or adjunctive treatment modality in veterinary care. Highlights: PEMF treatment is increasingly being used for both human and veterinary care. PEMF devices deliver electromagnetic fields to tissue to promote healing. Basic and clinical research on PEMF treatment has matured over the last decade. Evidence supports PEMF treatment for fractures, pain, wounds, and other indications. PEMF, as part of multimodal treatment, may improve veterinary clinical outcomes.